2016
DOI: 10.1136/heartjnl-2016-309945
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in prodromal symptoms in acute coronary syndrome in patients aged 55 years or younger

Abstract: Prior to ACS, women were more likely to experience prodromal symptoms and seek medical attention than men. Prehospital care was generally similar between sexes but demonstrated underutilisation of risk-reduction therapies in at-risk young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 27 publications
1
43
1
2
Order By: Relevance
“…In young women, the most common prodromal symptom leading up to the AMI is fatigue. 42 Additionally, in the month prior to presentation of AMI, young women have a poorer health status and worse psychosocial status than men. Specifically, women report worse physical/mental functioning, more angina, worse physical limitations, and a poorer quality of life prior to their AMI.…”
Section: Pre-ami Factorsmentioning
confidence: 99%
“…In young women, the most common prodromal symptom leading up to the AMI is fatigue. 42 Additionally, in the month prior to presentation of AMI, young women have a poorer health status and worse psychosocial status than men. Specifically, women report worse physical/mental functioning, more angina, worse physical limitations, and a poorer quality of life prior to their AMI.…”
Section: Pre-ami Factorsmentioning
confidence: 99%
“…However, women were more likely to present with more symptoms but less chest pain compared with men. 185 Similarly, compared with men, women ≤45 years of age with AMI are significantly more likely to present without chest pain and to have higher in-hospital mortality. 41 A qualitative study of women 30 to 55 years of age with AMI found that although they reported a diverse range of symptoms from discomfort or pain (eg, chest, neck and jaw) to more general symptoms (eg, sweating, anxiety, fatigue, and dizziness), the majority reported chest pain.…”
Section: Symptoms Of Amimentioning
confidence: 99%
“…[184][185][186] Although most patients with AMI present with typical chest pain or chest discomfort, women often present with atypical chest pain and anginaequivalent symptoms such as dyspnea, weakness, fatigue, and indigestion, as illustrated in Table 1. 187 Sex differences in clinical presentation have consequences for timely identification of ischemic symptoms, appropriate triage, and judicious diagnostic testing and management.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Of course, women may also be somewhat more likely to experience atypical symptoms, such as nausea, shortness of breath, and back pain in the setting of ischemia, though data are mixed in terms of the degree to which this differs from men's symptom experience, [6][7][8][9] and women with myocardial infarction (MI) are more likely than men to present without chest pain. 10,11 This is particularly important because the absence of chest pain as a presenting symptom has been associated with increased mortality, especially among younger women with MI. 10 Overall, though, the similarities far outweigh the differences, and although women may be slightly more likely to fit into this atypical category, both sexes need to know that atypical symptoms are common.…”
Section: Awareness and Recognition Of Cardiac Symptomsmentioning
confidence: 99%